Exoticism in Parisian Movie Theaters between the Two World Wars - Abadie, Shahram (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2018)
This article examines, through the study of the Parisian case, the idea according to which the exoticism would have marked an important phase of the cinema architecture during the interwar period. The aim is to highlight the reasons and the scope of this trend by analyzing the history of the architects and sponsors of the cinema and its architecture in the context of international exchanges. The paper concludes with the issue of the reception and the destiny of these examples of exoticism. The methodology consists of crossing our doctoral research with existing work on exoticism and orientalism in Western art. This synthesis has shown that the use of exotic motifs in Parisian cinemas is relatively early, but this decorative mode remains marginal compared to the Art Deco trend. However, although all their first owners have failed, the uniqueness of these cinemas has guaranteed their survival and preservation as an architectural and cinematographic heritage.